Pengaruh Pembelajaran PjBL berbasis Green Curriculum dalam Mata Pelajaran IPA dalam Menumbuhkembangkan Metakognitif Santri Pondok Pesantren - Arga Triyandana; Amang Fathurrohman; Nuril Hidayati (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Abstract Purpose: This study investigates the effect of implementing Green Curriculum-based Project Based Learning (PjBL) on the development of metacognitive skills among students at PIQ Singosari Malang Islamic Boarding School, while simultaneously fostering environmental awareness through practical ecological projects. Design/methodology/approach: The research employed a quasi-experimental design with pretest-posttest nonequivalent control group model, involving 50 students divided into experimental and control groups. Data were collected using the validated Metacognitive Awareness Inventory and analyzed through independent samples t-test to compare mean differences in metacognitive skills between groups receiving Green Curriculum-integrated PjBL and conventional instruction. Research limitations/implications: While limited by sample size and intervention duration, the findings strongly suggest that integrating Green Curriculum with PjBL effectively enhances metacognitive skills. This implies that educators should consider incorporating environmental projects into science education to simultaneously develop cognitive abilities and ecological awareness. Findings: The results demonstrated statistically significant improvements in the experimental group across all metacognitive dimensions, with planning showing a mean difference of 9.08 (p=0.012), monitoring 13.72 (p=0.001), and evaluation 24.52 (p=0.000). The 95% confidence intervals confirmed the reliability of these differences, indicating substantial enhancement in students' abilities to plan, monitor, and evaluate their learning processes. Originality/value: This study presents a novel integration of Green Curriculum with PjBL specifically designed for Islamic educational contexts, offering empirical evidence of how environmental projects enhance metacognitive abilities while aligning with Islamic environmental values, thus providing a replicable model for sustainable education development